2012
DOI: 10.4048/jbc.2012.15.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Findings of Invasive Micropapillary Carcinoma of the Breast

Abstract: PurposeThe purpose of this study is to evaluate imaging and histopathologic findings including the immunohistochemical characteristics of invasive micropapillary carcinoma (IMPC) of the breast.MethodsTwenty-nine patients diagnosed with IMPC were included in the present study. Mammographic, sonographic, and magnetic resonance imaging (MRI) findings were analyzed retrospectively according to the American College of Radiology Breast Imaging Reporting and Data System lexicon. 18F-fluorodeoxyglucose positron emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 20 publications
4
31
2
Order By: Relevance
“…Even though the imaging characteristics of IMPC are not distinguishable from that of IDC-NOS, positron emission tomography-computed tomography might be helpful in the diagnosis by identifying the high maximum standardized uptake value, which is apparent as a feature of IMPC because of its frequent LVI and LNM. 11 Most patients with IMPC present with axillary LNM at initial diagnosis, and LNM is the most important prognosis predictor of IMPC. Chen et al 9 identified LNM in 84.8% (84 of 99) of the IMPC cases, significantly higher than that in 50% (50 of 100; P , .001) in IDC-NOS cases.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Even though the imaging characteristics of IMPC are not distinguishable from that of IDC-NOS, positron emission tomography-computed tomography might be helpful in the diagnosis by identifying the high maximum standardized uptake value, which is apparent as a feature of IMPC because of its frequent LVI and LNM. 11 Most patients with IMPC present with axillary LNM at initial diagnosis, and LNM is the most important prognosis predictor of IMPC. Chen et al 9 identified LNM in 84.8% (84 of 99) of the IMPC cases, significantly higher than that in 50% (50 of 100; P , .001) in IDC-NOS cases.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…However, in the literature, no consensus has been reached regarding the amount of IMPC tissue in the breast carcinoma required to make a diagnosis and determine the type of IMPC ( 5 ). IMPC is associated with a high incidence of axillary lymph node metastases and local recurrence and poor clinical outcome ( 6 ). These clinical characteristics indicate the significance of IMPC being recognised by surgeons and pathologists.…”
Section: Introductionmentioning
confidence: 99%
“…Although this carcinoma is rare, it is clinically significant because of the high frequency of lymphovascular invasion, axillary nodal metastasis, and locoregional recurrence, as well as the poor prognosis [ 13 ]. It has been reported that mammographic, ultrasonographic, and magnetic resonance imaging findings of invasive micropapillary carcinoma are highly suggestive of malignancy and no feature to distinguish invasive micropapillary carcinoma from typical invasive ductal carcinoma has yet been described [ 14 ].…”
Section: Discussionmentioning
confidence: 99%